2007
DOI: 10.1182/blood-2006-10-051649
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell–derived human granzyme H induces an alternative, caspase-independent cell-death program

Abstract: IntroductionGranzyme H (GzmH) is regarded as an orphan granzyme with unknown biologic functions in immune defense cells. 1 Recent reports show that this serine protease is predominantly expressed at high levels in natural killer (NK) cells and has chymotrypsin-like (chymase) activity. 2 No functional studies have as yet been reported. Granzymes (granule enzymes) are of particular interest due to their different proteolytic specificities and potential abilities to trigger cell death in tumor and virally infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 39 publications
6
78
0
Order By: Relevance
“…Rapid mitochondrial swelling and disruption of mitochondrial ultrastructure are particularly striking in cells treated with GzmC. The mitochondrial pathways activated by GzmC and GzmH may be different; GzmC has been reported to trigger cytochrome c release, a sign of MOMP, whereas GzmH does not seem to cause cytochrome c release (159,160).…”
Section: Granzymes C and Hmentioning
confidence: 99%
See 3 more Smart Citations
“…Rapid mitochondrial swelling and disruption of mitochondrial ultrastructure are particularly striking in cells treated with GzmC. The mitochondrial pathways activated by GzmC and GzmH may be different; GzmC has been reported to trigger cytochrome c release, a sign of MOMP, whereas GzmH does not seem to cause cytochrome c release (159,160).…”
Section: Granzymes C and Hmentioning
confidence: 99%
“…Mouse GzmC and human GzmH, homologous granzymes that lie downstream from GzmB, are predicted to have chymotryptic activity and cleave substrates after aromatic residues (159,160). GzmH is thought to have arisen during primate evolution, independently of GzmC, in an intergenic recombination event between GzmB and a mast cell chymase (161).…”
Section: Granzymes C and Hmentioning
confidence: 99%
See 2 more Smart Citations
“…50,51 To date, two groups have assessed the cytotoxic potential and mechanism of action of purified recombinant GrH. 52,53 Interestingly, some of their findings were highly disparate. Both groups observed that GrH cytotoxicity resulted in phosphatidylserine exposure, some loss of plasma membrane integrity, chromatin condensation, DNA damage (although they observed different patterns), and mitochondrial damage.…”
Section: Mechanisms Of Cytotoxicity and Physiological Roles Of Grsmentioning
confidence: 99%